Rentiership and intellectual monopoly in contemporary capitalism: Conceptual challenges and empirical possibilities - Joseph Baines; Sandy Brian Hager (City, University of London, City Political Economy Research Centre (CITYPERC), 2023)
The concepts of rentiership and intellectual monopoly have gained increased prominence in discussions about the transformation of global capitalism in recent years. However, there have been few if any attempts to construct measures for rentiership and intellectual monopoly using firm-level financial data. The absence of such work, we argue, is symptomatic of conceptual challenges in delineating what precisely qualifies as rent, intellectual or otherwise. In place of static conceptions of rent and intellectual monopoly, we develop a dynamic framework for analyzing the processes of rentierization and intellectual monopolization and apply this framework to the analysis of the transformation of non-financial firms in the United States since the 1950s. We find that the timing and intensity of rentierization and intellectual monopolization differs significantly across sector and firm size and is heavily mediated by the uneven ramifications of government policy across companies and industries. Overall, our framework illuminates the variegated landscape of corporate power in the US, and offers a useful guide for critically interrogating rentierization and intellectual monopolization in other contexts.
Keywords: 330